Studies of craniofacial gene expression during embryonic development in divergent Arctic charr (Salvelinus alpinus) morphs - Ahi, Ehsan Pashay, 1983- (2016)
Arctic charr, Salvelinus alpinus, is a northern freshwater fish species exhibiting remarkable morphological variation. In particular this applies to in the head and trophic apparatus and often relates to benthic versus limnetic habitats. In Lake Thingvallavatn, four morphs of Arctic charr are found; two benthic morphs with subterminal mouth and blunt snout and two limnetic morphs with a terminal mouth. The aim of this study was to investigate the molecular basis of this diversification as seen in gene expression during craniofacial development. First, genes with stable expression were validated for quantitative real-time PCR (qPCR) analysis during craniofacial development of contrasting Arctic charr morphs. In this study, two genes with roles in craniofacial skeletogenesis, Mmp2 and Sparc, were found to have higher expression in developing heads of benthic morphs. Secondly, whole embryo transcriptome data were obtained from two contrasting morphs. This provided a collection of differentially expressed genes for targeted gene expression studies in the developing head. Building on these findings and screening of co-expression data available for vertebrate model species a conserved co-expression network of genes associated with the benthic-limnetic axis of divergence in developing heads of Arctic charr morphs was identified. Lastly, a study was designed to investigate whether the identified network could be part of a larger molecular pathway involved in craniofacial skeletogenesis. The results suggest differential regulation of the Aryl hydrocarbon signalling pathway, during embryonic development, as a potential mechanism affecting craniofacial morphological divergence in sympatric Arctic charr morphs. The Icelandic Centre for Research (RANNIS), The University of Iceland Research Fund, The Eimskip University Fund